Promouvoir la durabilité par l’analyse du cycle de vie des produits - Michel Gueldry; James Knuckles (VertigO)
In this article, we propose a way to analyze the impact of a product’s life cycle on the triple bottom line (social, environmental, and economic) — that corporate sustainability concept so often described as the reconciliation of the Triple P (People, Planet, and Profit) — to move beyond the excesses and contradictions inherent to the current unsustainable system, which can be described as the Triple C (Carboniferous Consumer Capitalism). Our analysis of the inputs and outputs that constitute a product’s life cycle connects the three complementary dimensions identified by Hendrickson et al., namely “inventory, impact, and improvement.” In this manner, we first situate our analysis among the predominant ideas in the field of life cycle analysis (LCA). We then propose a link between the LCA inputs/outputs inventory and its broader impacts, or, as Marc J. Epstein and Bill Birchard, well-known corporate social responsibility consultants in the United States, write, “counting what counts.” This LCA evaluation allows for a discussion of the practical improvement of business operations through an integrated accounting of what counts. Our methodology facilitates a decision hierarchy, and offers a way to minimize the negative impacts of a product’s life cycle, to augment the positive impact of a product’s life cycle, and, finally, to serve a greater end than just profit maximization.